“Remembering the Poor” (Gal. 2:10): Pauline Preaching of an Integral Gospel - Swetnam, James (Journal of Dharma, 2008)
Saviour Menachery, “Remembering the Poor” (Gal. 2:10): Pauline Preaching of an Integral Gospel, Vatican: Libreria Editrice Vaticana, 2009, pages: xix + 219, ISBN: 978-88-209-8153-2.